On theology and psychology : : a correspondence - Jung, C. G. (Carl Gustav), 1875-1961 (Philemon Foundation Ser., 2020)
"This book collects highlights from the fifty-year correspondence between C. G. Jung (1875- 1961) and his friend Adolf Keller (1872-1963), a celebrated Swiss theologian who was one of the founders of the modern ecumenical movement. Keller was one of the first religious leaders to become interested in Jungian psychoanalysis. He eventually became a pioneer of pastoral psychology and a major player in the World Council of Churches in the postwar era. The two first met as young men in 1907. Keller sided with Jung after the latter's break with Freud and he later played an active role in Jung's Zurich school. For many years Keller was the only theologian of stature to align himself with Jung; Keller's wife went on to become a psychiatrist and Jungian psychotherapist. The letters reveal an extended intellectual and spiritual dialogue between the two men as they exchange views on the nature of God, the compatibility of Jungian psychology and Christianity, the interpretation of the Bible, and the phenomenon of National Socialism. Although Keller was powerfully attracted to Jungian ideas the letters show that he avoided discipleship. The book begins with an introduction by volume editor Marianne Jehle that provides context to this meeting of psychology and Protestant theology"--